Human Immunodeficiency Virus / Acquired Immunodeficiency Syndrome Prevention Behavior among Men Who Have Sex with Men (MSM) in the Gender Sexuality Group Community - Herman, Herman; Fadilah, Nur; Fikri, Mohammad (Journal of Health and Nutrition Research, 2024)
Between January-August 2019, Central Sulawesi Province recorded 235 HIV and 94 AIDS cases. Data from the Gender Sexuality Group indicates that their community houses 28 MSM, 18 of whom are living with HIV/AIDS. This research seeks to understand HIV/AIDS prevention behaviors among MSM at the Gender Sexuality Group Community in Palu City. A qualitative case study approach was employed, with data collection through triangulation techniques including in-depth interviews, observation, and documentation using interview guides. Results show that MSM within the Gender Sexuality Group community demonstrate good knowledge of HIV/AIDS prevention. However, four out of seven informants still engage in risky behaviors. To address this, community and healthcare workers need to provide better infrastructure for HIV/AIDS prevention and treatment, especially for MSM living with HIV. Collaborative support from healthcare workers and the community is crucial in strengthening and assisting MSM. It's recommended that the Gender Sexuality Group community continues to conduct Communication, Information, and Education (CIE) activities to enhance MSM knowledge, particularly about HIV transmission and prevention. All MSM should undergo HIV testing at least twice a year. The community could organize seminars featuring disguised MSM PLWHA (People Living with HIV/AIDS) from outside the city as resource persons to increase awareness about HIV/AIDS within the key community